Teacher Problematics in Applying Authentic Assessment in Curriculum 2013 of Class IV State Elementary School in Serang Subdistrict (Universitas Negeri Semarang, 2019)
This study aims to analyze the teacher's understanding of authentic assessment, analyze the process of applying authentic assessment, identify teacher problems in applying authentic assessments and the efforts of teachers and principals to address teacher problems in applying authentic judgments. The type of research is qualitative research and phenomenological research design. The subject from this study were grade IV teachers and the elementary school principals in Serang Subdistrict. Data collection techniques used are structured interview methods, observation, and documentation. The technique of checking the validity of the data uses source and method triangulation techniques. Data analysis techniques carried out during the study include data reduction, data presentation, and conclusions. The results showed that the teacher understanding of authentic assessment was good but not maximal, the teacher used the assessment instrument in accordance with the guidelines in Curriculum 2013, the application of authentic Public Elementary School in Serang Subdistrict had gone well, but some things were still constrained, teacher problems in applying authentic assessment, teacher efforts are questioned and answer with colleagues, seeking information from other sources, following the data update and workshops, training and training using computer. The principal's efforts are as follows: understanding the difficulties of the teacher, finding examples of appraisal applications, finding friends to explain, giving the assessment manual giving supervision to the teacher and giving evaluations to the teacher.